2017
DOI: 10.1001/jamapsychiatry.2017.0044
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Self-guided Internet-Based Cognitive Behavioral Therapy in the Treatment of Depressive Symptoms

Abstract: IMPORTANCE Self-guided internet-based cognitive behavioral therapy (iCBT) has the potential to increase access and availability of evidence-based therapy and reduce the cost of depression treatment.OBJECTIVES To estimate the effect of self-guided iCBT in treating adults with depressive symptoms compared with controls and evaluate the moderating effects of treatment outcome and response.DATA SOURCES A total of 13 384 abstracts were retrieved through a systematic literature search in PubMed, Embase, PsycINFO, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
468
9
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 624 publications
(526 citation statements)
references
References 52 publications
25
468
9
11
Order By: Relevance
“…As was the case in this study, implementing a iCBT intervention with support ensures sufficient monitoring and the potential to intervene if necessary with a vulnerable population at greater risk than those with mild and moderate depression [21]. It is relatively unknown whether individuals with severe depression benefit more, or less from support than those in the mild to moderate range, though recent analyses has suggested that there is no difference in how different populations of severity benefit [39]. Further research would be helpful to delineate mechanisms associated with internet-delivered interventions and how they fluctuate depending on the population and severity.…”
Section: Discussionmentioning
confidence: 77%
“…As was the case in this study, implementing a iCBT intervention with support ensures sufficient monitoring and the potential to intervene if necessary with a vulnerable population at greater risk than those with mild and moderate depression [21]. It is relatively unknown whether individuals with severe depression benefit more, or less from support than those in the mild to moderate range, though recent analyses has suggested that there is no difference in how different populations of severity benefit [39]. Further research would be helpful to delineate mechanisms associated with internet-delivered interventions and how they fluctuate depending on the population and severity.…”
Section: Discussionmentioning
confidence: 77%
“…Randomized controlled trials (RCTs) exploring the efficacy of self-guided iCBT for depression in adults were obtained by referencing the latest meta-analysis of self-guided iCBT for depression [16]. These authors consulted a database of psychological treatments for depression which was constructed from a systematic literature search of PubMed, Embase, PsycINFO, and Cochrane Library updated until January 1, 2016.…”
Section: Methodsmentioning
confidence: 99%
“…A major advancement in the study of treatments for depression is the discovery that selfguided internet-based cognitive-behavioral therapy (iCBT) can be more effective than control conditions [16]. In these interventions, patients complete interactive online programs based on the principles of cognitive-behavioral therapy (CBT) with no therapeutic support, though technical support is sometimes available.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interest in applying digital technologies to psychiatric practice has been increasing since the early 2000s, and recommendations for future research in this area were issued in 2013 by a technical expert panel convened by the Agency for Healthcare Research and Quality and the National Institute of Mental Health [10][11][12]. Examples of interventions that have used DHTs in patients with SMI include ecological momentary assessment and treatment interventions [13], computerized psychotherapies [14], cognitive remediation [15,16], family psychoeducation interventions [17], and interventions specifically targeting medication adherence [18].…”
Section: The Potential Of Digital Health Tools For Psychiatric Practicementioning
confidence: 99%